Isolation and Chracterization of Pyocyanine and 1-Phenazinole From Pseudomonas Aeruginosa (An Endophyte) - Eshagid, Majid (1998)

(untitled)
Endophytic bacteria are organisms that colonize internal plant tissues. These organisms are believed to be useful for pharmacological screening and agricultural programs for biological control of plant pests and diseases. This project was designed to screen endophytic bacteria to be used for pharmaceutical purpose. Bacterial endophytes were isolated from the twigs of 50 different healthy tropical rain forest plants collected at Kemensal Hill, Ulu Kelang, Selangor. After preparing the pure culture of the bacteria, the isolates were subjected to bioassay using disk diffusion method against Bacillus cereus NRRL 1447 (Gram-positive bacteria), Pseudomonas aeruginosa ATCC 60690 (Gram-negative bacteria), Bacillus subtilis B₂₈ and B₂₉ [mutant (deficient in DNA repair) and wild type], Candida lipolytica ATCC 2075 (yeast), Sacchromyces /ipolytica ATCC 16617 (yeast) and Aspergillus ochraceous ATCC 398 (fungi). Out of the 79 bacterial endophytes that were isolated from 50 tropical plants, 12 of them showed antimicrobial activity. One of the isolate (no.32.1) that possesses the best inhibition activity against target microorganisms was selected for further study. By employing biochemical tests, miniaturized multi test system (API 20NE kit) and whole cellular fatty acid profiles the isolate was identified as Pseudomonas aeruginosa UPM strain. Judicious combinations of chromatographic techniques were adopted in purifying the active compounds from the fermentation media. As a result, two bioactive compounds were purified. The structure of these two bioactive compounds were elucidated by means of spectroscopic techniques including ultraviolet spectroscopy (UV), infrared spectroscopy (IR), nuclear magnetic resonance spectroscopy (¹H and ¹³C-NMR), mass spectroscopy (MS), also by comparison with the literature and they were identified as pyocyanine and I-phenazinole. Minimum inhibitory concentration of pyocyanine against P. aeruginosa, B. subtilis (B₂₉) and methicillin resistant Staphylococcus auerus was 4.6875 µg/disk, while against B. subtilis (B₂₈) and B. cereus was 9.375 µg/disk. I-Phenazinole had the MIC value of 37.5 µg/disk against P. aeruginosa, C. lipolytica, A. ochraceous. The MIC value of this compound was 75 and 150 µg/disk against B. cereus, B. subtilis (B₂₈ and B₂₉), S. lipolytica and MRSA, respectively. Therefore, pyocyanine revealed antibacterial activity whereas, I-phenazinole was active against all target microbes. The antimicrobial activity of I-phenazinole was less than pyocyanine. The cytotoxicity of the compounds were tested against the HeLa cells (Human cervical adenocarcinoma), 3T3 (Mouse fibroblast), T-Lymphoblastic Leukemic cells (CEM-SS) and Sf9 insect cells. 1-Phenazinole was found to be more toxic than pyocyanine against the tested cell lines, except for CEM-SS. Cytotoxic activity of the compounds against 3T3 cell line (noncancerous mouse fibroblast) was lower than against the tumor cell lines. Thus, the compounds revealed fairly selective cytotoxic activity against tumor cell lines. The compounds showed cytotoxic effect on Sf9 insect cells and therefore could be used for biological control